Tinjauan Hukum Islam Terhadap Sistem Pengupahan dalam Perjanjian Kerja CV Habeha Multimedia Desa Wonolelo Kecamatan Wonosobo Kabupaten Wonosobo - Tri Hargiyani (At-Ta’awun: Jurnal Mu’amalah dan Hukum Islam, 2026)
This study aims to analyze the wage system in employment agreements at CV Habeha Multimedia and examine its compliance with Islamic law. This research uses a field research method with a descriptive qualitative approach through interviews, observations, and documentation.The results show that the employment agreement has been made in written form and includes the rights and obligations of both parties. However, in practice, there are still delays in wage payments and wages that do not meet the applicable minimum standards.From the perspective of Islamic law, the wage system generally fulfills the pillars and requirements of ijarah (employment contract). However, delays in wage payments contradict the principles of justice and timeliness in Islam. Therefore, improvements are needed in the implementation of the wage system to ensure compliance with Sharia principles.